Identifying silver ore sources for the earliest coins of Athens - Gillan Davis; Janne Blichert-Toft; Liesel Gentelli; Damian B. Gore; Kenneth A. Sheedy; Francis Albarède (Archaeological and Anthropological Sciences, 2025)
This study addresses longstanding questions concerning the ore sources used in the first series of coins of ancient Athens known as the Wappenmϋnzen (c.540-c.500 BCE) by combining comprehensive numismatic data on 22 coins (16 new and 6 legacy analyses) with lead isotope and surface elemental measurements (MC-ICP-MS and XRF). It finds usage of ores from Spain to Romania and Türkiye and frequent mixing. This upends current thinking based on a (mis)interpretation of historical sources which argues that the tyrant Peisistratos and his sons, who ruled Athens during the period, sourced most silver from the districts of Mt Pangaion and Strymon River in northern Greece and that silver did not flow from the western Mediterranean into their coinage. The data suggest that domestic ‘Lavrion’ mines of Athens did not contribute to the ore stock of the Wappenmϋnzen until the subsequent production of the ‘owl’ series when it was also used in some Wappenmϋnzen fractions and show that there is no correlation between coin types and ore sources. Elemental compositions nuance our understanding of the coins, but do not shed light on provenance. Together, these new findings force a reappraisal of numismatic and historical perceptions of the period of the Athenian tyranny in the lead up to democracy, not least because the multiple silver sources point to trading relationships with a greater variety of regions than previously contemplated.